The Role of English for Forestry Students: A Needs Analysis in East Borneo (LITPAM, 2025)
In the context of globalization, this research emphasizes the crucial relevance of solid English abilities, highlighting the function that English plays as a core discipline in higher education. In order to achieve learning objectives and aims, the research is primarily concerned with resolving difficulties that are relevant to students. The purpose of this research is to specifically explore the function that English plays in the area of forestry by exploring Need Analysis among Forestry students in Mulawarman University. The study reveals key findings by employing tools such as questionnaires and observation checklists. These findings include a high level of motivation and persistence among Forestry students in the process of learning English, proficient grammar skills, a future emphasis on communication skills, and the prevalence of English usage in international conferences and workshops within the forestry domain. Not only do these findings offer to a more nuanced understanding of the role of English in forestry education, but they also influence efficient methods of teaching English for Specific Purpose.